Neuro-Education and Neuro-Rehabilitation - Mireille Besson (Frontiers Research Topics, 2016)
In the last decade, important discoveries have been made in cognitive neuroscience regarding brain plasticity and learning such as the mirror neurons system and the anatomo-functional organization of perceptual, cognitive and motor abilities.... Time has come to consider the societal impact of these findings. The aim of this Research Topic of Frontiers in Psychology is to concentrate on two domains: neuro-education and neuro-rehabilitation. At the interface between neuroscience, psychology and education, neuro-education is a new inter-disciplinary emerging field that aims at developing new education programs based on results from cognitive neuroscience and psychology. For instance, brain-based learning methods are flourishing but few have been rigorously tested using well-controlled procedures. Authors of this Research Topic will present their latest findings in this domain using rigorously controlled experiments. Neuro-rehabilitation aims at developing new rehabilitation methods for children and adults with learning disorders. Neuro-rehabilitation programs can be based upon a relatively low number of patients and controls or on large clinical trials to test for the efficiency of new treatments. These projects may also aim at testing the efficiency of video-games and of new methods such as Trans Magnetic Stimulation (TMS) for therapeutic interventions in children or adolescents with learning disabilities. This Research Topic will bring together neuroscientists interested in brain plasticity and the effects of training, psychologists working with adults as well as with normally developing children and children with learning disabilities as well as education researchers directly confronted with the efficiency of education programs. The goal for each author is to describe the state of the art in his/her specific research domain and to illustrate how her/his research findings can impact education in the classroom or rehabilitation of children and adolescents with learning disorders.